Hydrogen Bond Mediated Aglycone Delivery: Synthesis of Linear and Branched α‐Glucans1. Issue 39 (12th August 2014) - Yasomanee, Jagodige P.; Demchenko, Alexei V.
Abstract A Hydrogen bond mediated aglycone delivery (HAD) method was applied to the synthesis of α‐glucans, which are abundant in nature, but as targets represent a notable challenge to chemists. The synthesis of linear oligosaccharide sequences was accomplished in complete stereoselectivity in all glycosylations. The efficacy of HAD may diminish with the increased bulk of the glycosyl acceptor, and may be an important factor for the syntheses of oligomers beyond pentasaccharides. The synthesis of a branched structure proved more challenging, particularly with bulky trisaccharide acceptors.